Ferromagnetism in CVT grown tungsten diselenide single crystals with nickel doping. (5th February 2018) - Habib, Muhammad; Muhammad, Zahir; Khan, Rashid; Wu, Chuanqiang; ur Rehman, Zia; Zhou, Yu; Liu, Hengjie; Song, Li
Abstract: Two dimensional (2D) single crystal layered transition materials have had extensive consideration owing to their interesting magnetic properties, originating from their lattices and strong spin–orbit coupling, which make them of vital importance for spintronic applications. Herein, we present synthesis of a highly crystalline tungsten diselenide layered single crystal grown by chemical vapor transport technique and doped with nickel (Ni) to tailor its magnetic properties. The pristine WSe2 single crystal and Ni-doped crystal were characterized and analyzed for magnetic properties using both experimental and computational aspects. It was found that the magnetic behavior of the 2D layered WSe2 crystal changed from diamagnetic to ferromagnetic after Ni-doping at all tested temperatures. Moreover, first principle density functional theory (DFT) calculations further confirmed the origin of room temperature ferromagnetism of Ni-doped WSe2, where the d -orbitals of the doped Ni atom promoted the spin moment and thus largely contributed to the magnetism change in the 2D layered material.